“ADVANTAGES OF AUTOMATION OF EDUCATIONAL MANAGEMENT BASED ON DIGITAL TECHNOLOGIES” (Modern American Journal of Engineering, Technology, and Innovation, 2025)
The article discusses the key advantages of automating educational management through digital technologies. It highlights how automation enhances data accuracy, decision-making, transparency, and operational efficiency in the education sector.